Adsorption of Toxic Metal Ions From Solution by Inactivated Cells of Larrea Tridentata Creosote Bush - J. L. Gardea-Torresdey; A. Hernandez; K. J. Tiemann; J. Bibb; O. Rodriguez (Journal of Hazardous Substance Research, 1998)
Larrea tridentata (creosote bush) is a plant that grows abundantly in the desert environment. This desert plant has been found naturally growing in heavy-metal contaminated soils. Previous experiments showed that the inactivated biomass of creosote bush was able to adsorb Cu(II) ions from aqueous solutions. The copper-binding capacity of the bush biomass that grows in heavy-metal uncontaminated soils was higher than the biomass that grows in heavy-metal contaminated soils. Experiments were performed to determine the ability of creosote bush biomass (grown in heavy metal uncontaminated soils) to adsorb Pb(II), Cd(II), Zn(II), Cr(III), Cr(VI), and Ni(II) ions from aqueous solutions. Batch pH profile experiments for these metal ions showed that the metal ion binding was different for every metal tested but increased as the pH was raised from 2.0 to 6.0. The metal ion uptake by the roots, stems, and leaves was quite fast. Binding capacity experiments showed a more significant binding capacity for lead(II) and chromium(III) ions and in general, the leaves bound more metal ions than the stems and roots. A great portion of the metal ions adsorbed by the creosote’s roots, stems, and leaves was desorbed by treatment with 0.1 M HCl (up to 99% in some cases). Biomass of creosote bush may prove to be useful to remove and recover metal ions from contaminated waters.
Keywords: Phytoremediation; Larrea tridentata; creosote bush; heavy metal binding